Membangun Integritas Karyawan Melalui Peran Si Peri di Baitul Maal wat Tamwil Nuansa Umat (BMT NU) Cabang Tegalsiwalan Probolinggo - Siti Murniatin; Indah Roziah Cholilah (Fakultas Dakwah UIN KHAS Jember, 2025)
This study aims to determine how to build employee integrity through the role of Si Peri in Baitul Maal wat Tamwil Nuansa Umat (BMT NU) Tegalsiwalan Probolinggo Branch. This study uses a descriptive qualitative method approach with data collection techniques used, namely semi-structured interviews, observation and documentation. Based on the results of the findings that researchers conducted at Baitul Maal wat Tamwil Nuansa Umat (BMT NU) Tegalsiwalan Branch, building employee integrity in accordance with the existing work culture, namely: Shiddiq, Amanah, fathonah, tabligh, istiqamah. In line with the theory put forward by Rogers regarding integrity, namely: Honest, Firm, Self Control, Self Esteem. The conclusion of the data obtained from interviews and observations substantially answers the focus of the study, although the role of the branch head and the work culture implemented by employees as work principles also have an influence, but Si Peri (External and Internal Control Systems) remains the dominant factor in building employee integrity.